Development of a Conceptual Model of Compliance with the Use of Personal Protective Equipment: A SEM-Based Study in Improving Occupational Safety of Health Workers - Nabilatul Fanny; Liss Dyah Dewi Arini; Muclas Adi Saputra; Muhamat Ramdani Hidayat (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to develop a conceptual model describing the relationship between Awareness, Compliance with PPE Use, Risk Perception, Organizational Support, Barriers and Attitudes and Compliance in improving occupational safety of healthcare workers. Using a Structural Equation Modeling (SEM) approach, this study investigates the influence of six latent factors, namely awareness, compliance behavior, risk perception, organizational support, barriers, and attitudes/motivation on occupational safety. A cross-sectional survey was conducted on 33 nurses at Dian Pertiwi Hospital, Karanganyar, Indonesia, using a Likert-scale questionnaire. Data were analyzed using SPSS and SmartPLS for construct validation and model testing. Reliability analysis showed that most constructs achieved Cronbach's Alpha ≥ 0.7, except for Risk Perception (α=0.693) and Attitude/Motivation (α=0.439), which improved after refinement. SEM results (R²=0.2275) indicated that PPE awareness and compliance had a positive, though insignificant, effect on occupational safety (p>0.05). These findings suggest that awareness and compliance play a significant role in improving workplace safety, but organizational factors and motivational aspects also contribute to behavioral consistency. This study provides a validated conceptual framework for future interventions aimed at improving PPE compliance and safety culture in healthcare institutions.